2008
DOI: 10.1016/j.cell.2008.06.022
|View full text |Cite
|
Sign up to set email alerts
|

A Network of Nuclear Envelope Membrane Proteins Linking Centromeres to Microtubules

Abstract: Summary In the fission yeast S. pombe, nuclei are actively positioned at the cell center by microtubules. Here we show that cytoplasmic microtubules are mechanically coupled to the nuclear heterochromatin through proteins embedded in the nuclear envelope. This includes an integral outer nuclear membrane protein of the KASH family (Kms2) and two integral inner nuclear membrane proteins: the SUN-domain protein Sad1 and the novel, conserved protein Ima1. Ima1 specifically binds to heterochromatic regions and prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
184
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(200 citation statements)
references
References 44 publications
(50 reference statements)
14
184
1
Order By: Relevance
“…Also, whereas nesprin-2G levels are somewhat reduced in lamin A/C-deficient cells, increasing nesprin-2G levels did not rescue nuclear movement, showing that lamin A/C plays a role beyond simply localizing nesprin-2G to the nucleus. There is precedent for anchoring of nesprin and SUN proteins to resist force: In Schizosaccharomyces pombe, orthologs of nesprins and SUN proteins are anchored by Ima1, a heterochromatin-binding protein (35). Given that lamin A/C interacts with heterochromatin, it will be interesting to see whether heterochromatin-binding proteins are also involved in anchoring TAN lines in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…Also, whereas nesprin-2G levels are somewhat reduced in lamin A/C-deficient cells, increasing nesprin-2G levels did not rescue nuclear movement, showing that lamin A/C plays a role beyond simply localizing nesprin-2G to the nucleus. There is precedent for anchoring of nesprin and SUN proteins to resist force: In Schizosaccharomyces pombe, orthologs of nesprins and SUN proteins are anchored by Ima1, a heterochromatin-binding protein (35). Given that lamin A/C interacts with heterochromatin, it will be interesting to see whether heterochromatin-binding proteins are also involved in anchoring TAN lines in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in flies, the SUN protein Klaroid is required for the localization of KASH protein Klarsicht to the NE and for nuclear migration in the eye (15). Genetic studies in the worm and yeast also have indicated roles of SUN proteins in mediating the interactions between the NE and centrosome, centromeres, and telomeres at various stages of mitotic and meiotic cells (16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…Similarly, in flies, the SUN protein Klaroid is required for the localization of KASH protein Klarsicht to the NE and for nuclear migration in the eye (15). Genetic studies in the worm and yeast also have indicated roles of SUN proteins in mediating the interactions between the NE and centrosome, centromeres, and telomeres at various stages of mitotic and meiotic cells (16)(17)(18)(19)(20)(21)(22).Mammalian SUN1 and SUN2 proteins were first identified as homologues of C. elegans UNC-84 (10). SUN1 and SUN2 are broadly distributed in mouse tissues, whereas 2 other, more recently identified SUN proteins, SUN3 and SPAG4, appear to be expressed in a limited amount of tissues (4,(23)(24)(25).…”
mentioning
confidence: 99%
“…Although most likely reside in the INM, several ONM proteins have been identified (7). These include members of the mammalian nesprin (or syne) family (8,9), Klarsicht (10) and Msp-300 (11,12) in Drosophila melanogaster, Anc-1 (13), Zyg-12 (14) and Unc-83 (15,16) in Caenorhabditis elegans, and Kms2 in the fission yeast Schizosaccharomyces pombe (17). A property that each of these has in common is that they interact with cytoskeletal components.…”
mentioning
confidence: 99%